A METHOD FOR STRATEGIC DECISION MAKING IN A WATERSHED -GAME THEORY - Arzu Basaran (European Regional Science Association (ERSA), 2005)
Rapid growth of urban areas and their development problems in industrializing countries has had major impacts on the environment. Water, the main source of life on earth is under the threat of various types of pollution. These threats have been forceful in demonstrating the necessity of the management and planning of drainage basins. The importance of the evaluation of the total economic value of the water resources and aquatic ecosystems of drainage basins has not yet been accepted in the current planning system of Turkey. In Turkey a total number of 36 public agencies take part in the decision making process within a drainage basin. Decisions taken by these agencies with respect to the use of land and water affect the quality and sustainability of water as a natural resource. These agencies act under a legal structure comprising 105 different laws and regulations related to the environment and this creates additional confusion in planning practice. The situation calls for the organization of special drainage management institutions for drainage basins. The aim of this study is to explore the use of game theory to analyze the roles and actions of different interest groups (players) and develop a better understanding of the decision making process and its consequences on a drainage basin. In this study, we use the case of a river sub-basin from the north-western region of Turkey: the Nilüfer Watershed that contains fertile agricultural lands and the third biggest industrial city in Turkey. The Nilüfer Stream is deeply polluted by industrial, agricultural and domestic wastewater. There are 1 metropolitan municipality, 20 district municipalities and 8 provincial authorities of central government within the watershed. All players have strategies about environment and planning such as land use decision, waste water standard and discharge permitting etc. Some strategies conflict the other players' strategies. Game theory, which aims to explain the interactive decision making process with more than one decision maker, has developed as a theory of human strategic behavior based on an idealized picture of rational decision making (Binmore, 1996; Eichberger, 1992). The game theory has been applied to social sciences especially to economy, international relations, politics, which are in the state of making decisions in non-cooperative conditions. Although there is limited in number the game theory applications in planning, they are very important studies on location problem in spatial planning such as Stevens, (1961), Isard and Reiner, (1962), Isard, (1967). There are also new studies that use the game theory in planning. Sharing problem of river as a natural resource is the main study area in planning (Dinar and Wolf, 1994; Kilot, 1994; Kucukmekmetoglu and Guldman, 2002; Rogers, 1993). Game theory applications on environmental problems started in 1990s. Environmental problems such as transfrontier pollution (air or water) are often multilateral, and they affect all the agents in the economies of countries. There are studies in which air pollution problem is analyzed by the game theory with the cooperation of neighbor countries such as Ray (2000), Maler and Zeeuw (1998), Barret (1998). In this research an in depth analysis is made to understand the preferences and attitudes of different players taking part within the Nilüfer watershed. Players generally make independent decisions without any form of cooperation situation. Therefore, non-cooperative game is used in this analyze. The decision making process of the players are analyzed through a scenario in two-player games. The scenario is about strategies of environmental protection and industrial development in the watershed. We explore Nash equilibrium in game which represents present condition. Nash (1950) proved the existence of a strategic equilibrium for non-cooperative games. The main outcome of the paper will be to point to new directions in the planning process and to open to discussion the use of game theory in planning. Game theoretic approach will make it easier for the agents to cooperate if the conflicts in the planned area are clearly defined. It is possible to achieve cooperative bargaining solutions where all agents are winners. Actually, this is the target of planning because sustainable development of the river basin depends on bargaining where all agents are winners.
Keywords: 330